A Smartphone-Based Obstacle Detection and Classification System for Assisting Visually Impaired People - Tapu, Ruxandra; Mocanu, Bogdan; Bursuc, Andrei; Zaharia, Titus (2013 IEEE International Conference on Computer Vision Workshops, 2013)
In this paper we introduce a real-time obstacle detection and classification system designed to assist visually impaired people to navigate safely, in indoor and outdoor environments, by handling a smartphone device. We start by selecting a set of interest points extracted from an image grid and tracked using the multiscale Lucas - Kanade algorithm. Then, we estimate the camera and background motion through a set of homographic transforms. Other types of movements are identified using an agglomerative clustering technique. Obstacles are marked as urgent or normal based on their distance to the subject and the associated motion vector orientation. Following, the detected obstacles are fed/sent to an object classifier. We incorporate HOG descriptor into the Bag of Visual Words (BoVW) retrieval framework and demonstrate how this combination may be used for obstacle classification in video streams. The experimental results demonstrate that our approach is effective in image sequences with significant camera motion and achieves high accuracy rates, while being computational efficient.